2011
DOI: 10.1007/s10750-010-0593-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substratum on the variability of benthic biofilm stable isotope signatures: implications for energy flow to a primary consumer

Abstract: Benthic biofilms have been identified using stable isotope analysis (SIA) as an important resource supporting many freshwater food webs. However, biofilm d 13 C signatures are highly variable in freshwaters, which may hamper our understanding of energy flow through food webs in these systems. There has been little consideration of the influence that substratum may have on biofilm d 13 C signature variability and energy flows to primary consumers. We investigated the effect of organic and inorganic substrata on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Variations in substrate composition can have a substantial influence on the biofilm community and subsequent benthic assemblages (Rahim et al 2004, Hladyz et al 2011. Katrina Reef was composed of limestone, Handkerchief Reef was composed of crushed concrete bridge materials, Legacy Reef was made of limestone rubble, and USM Reef was composed of limestone rock and oyster shells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in substrate composition can have a substantial influence on the biofilm community and subsequent benthic assemblages (Rahim et al 2004, Hladyz et al 2011. Katrina Reef was composed of limestone, Handkerchief Reef was composed of crushed concrete bridge materials, Legacy Reef was made of limestone rubble, and USM Reef was composed of limestone rock and oyster shells.…”
Section: Discussionmentioning
confidence: 99%
“…barnacles, mussels (see Rahim et al 2004, Burt et al 2009, Granneman and Steele 2015] which, over time, influence the diversity of a mature artificial reef's fauna. Hladyz et al (2011) reported that substrate composition is a crucial factor in marine biofilm development and later growth of the artificial reef; substrate differences revealed by stable isotope analysis have an effect on energy flow to primary consumers in aquatic food webs. Biofilm microbial communities are important in the production and decomposition of organic matter and in the cycling of limiting nutrients (Mouton et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We also collected epilithic biofilms, although given the diverse range of primary organic matter sources within biofilms and their potential to affect isotopic signatures (Hladyz et al, 2011), we classified biofilms as a mixture for the purpose of tracing primary organic matter sources. At each study reach, we sampled all visually abundant terrestrial organic matter sources along a 100 m length of stream, including soil, grasses, shrubs and trees.…”
Section: Stable Isotope Analysis Of Organic Matter Sources and Standimentioning
confidence: 99%
“…rocks) (Sabater et al, 1998). These heterotrophs may use the substrate directly as a carbon source, leading to a d 13 C value that resembles the substrate rather than the algae (Walters et al, 2007;Hladyz et al, 2011). One solution to this problem is a technique for purifying algae that employs colloidal silica to create a density gradient (Hamilton et al, , 2005, allowing the denser detritus to settle to the bottom of a collection tube during centrifugation.…”
Section: Discussionmentioning
confidence: 99%